2021
DOI: 10.1007/s00418-020-01960-z
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormones and human choriogonadotropin influence the distribution of alpha6-integrin and desmoplakin 1 in gland-like endometrial epithelial spheroids

Abstract: In human glandular endometrial epithelial cells, desmosomal and adherens junction proteins have been shown to extend from a subapically restricted lateral position to the entire lateral membrane during the implantation window of the menstrual cycle. Similarly, a menstrual cycle stage-dependent redistribution of the extracellular matrix adhesion protein α6-integrin has been reported. These changes are believed to be important for endometrial receptiveness and successful embryo implantation. To prove the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Overall, the rearrangement of the junctional complex may weaken cell-cell adhesion and prepare the endometrium for trophoblast invasion. Comparable alterations of junctional rearrangements were also observed in 3D in vitro cell models [26] (see also Figure 4). Thus, a redistribution of desmosomes and adherens junctions was documented in response to estrogen, progesterone, and a combination of both in 3D acini prepared from the moderately polarized endometrial epithelial cell line Ishikawa [26].…”
Section: Endometrial Epithelial Cells Change Junctional Arrangement To Become Receptivesupporting
confidence: 53%
See 1 more Smart Citation
“…Overall, the rearrangement of the junctional complex may weaken cell-cell adhesion and prepare the endometrium for trophoblast invasion. Comparable alterations of junctional rearrangements were also observed in 3D in vitro cell models [26] (see also Figure 4). Thus, a redistribution of desmosomes and adherens junctions was documented in response to estrogen, progesterone, and a combination of both in 3D acini prepared from the moderately polarized endometrial epithelial cell line Ishikawa [26].…”
Section: Endometrial Epithelial Cells Change Junctional Arrangement To Become Receptivesupporting
confidence: 53%
“…The partial epithelial-to-mesenchymal transition presumably reduces the barrier function of the endometrium for the embryo to implant. Manifestations of the structural and functional transition in the human endometrium include the downregulation of N-cadherin [18], changes in apical marker enzyme expression [19,20], the reduction of apical microvilli [21] with the development of large apical membrane protrusions referred to as pinopodes [22], increased plasma membrane tortuosity [23], cytoskeletal reorganization [6,24,25], changes in cell-extracellular matrix contacts [26], and the rearrangement of the tripartite junctional complex [27,28] (Figure 3).…”
Section: Endometrial Epithelial Cells Change Junctional Arrangement To Become Receptivementioning
confidence: 99%
“…In this regard, in earlier published work, Buck and colleagus used immunofluorescence microscopy to investigate the localization and distribution of endometrial epithelial junction proteins during the human menstrual cycle (Buck et al 2012), and further demonstrated the great utility of creating and using endometrial spheroids as a model system for studying human embryo implantation (Buck et al 2015). In their current investigation, Buck et al (2021) continue their use of the endometrial spheroid model to investigate the effect of steroid hormones and human choriogonadotropin on the polarity-inducing localization of cellular adhesion proteins. They created spheroid cultures from the Ishikawa human endometrial cell line, treated them with ovarian steroids or human choriogonadotropin, and then performed multilabel immunostaining followed by wide-field light microscopic imaging.…”
Section: Implanting the Idea Of Steroid Hormone Influence On Epithelial Cell Polaritymentioning
confidence: 89%
“…Among the various repair components and mechanisms, different chloride channels may be involved since they play a role in keratinocyte migration, proliferation, and differentiation (Dong et al 2015;Guo et al 2016;Pan et al 2015) as well as tumor suppression (Zhang et al 2013). The activity of the chloride channels seems to be regulated by various chloride channel accessory proteins (Patel et al 2009) that are also present in epidermal keratinocytes (Braun et al 2010;Connon et al 2004). Through their regulatory effect, they can modulate cell proliferation and apoptosis, and via their integrin-binding domains, they can promote cell adhesion and control migration and invasion.…”
Section: A Chloride Channel-associated Protein Keeps Keratinocytes Quietmentioning
confidence: 99%
See 1 more Smart Citation